2003
DOI: 10.1051/animres:2003012
|View full text |Cite
|
Sign up to set email alerts
|

Sward structural resistance and biting effort in grazing ruminants

Abstract: -Grazing ruminants face complex decisions in searching for and harvesting adequate forage to meet their requirements in the face of heterogeneity in the abundance, nutritive value and distribution of resources. Some of the major decisions which affect the bite mass and therefore, forage intake adjustments in bite depth, bite area and exerted bite force, are made in relation to heterogeneity in sward structure. A number of relationships have been established linking the adjustment of bite mechanics in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…We did not find any evidence to support the 'summit maximum bite force hypothesis' (Griffiths and Gordon, 2003) in vegetative swards of tropical pasture grass species. Hughes et al (1991) and Laca et al (1993) also found that bite area decreased in response to the increase in grazing resistance of the swards but a maximum bite force was not detected.…”
Section: Bite Dimensions and Selectivity Regulationcontrasting
confidence: 90%
See 2 more Smart Citations
“…We did not find any evidence to support the 'summit maximum bite force hypothesis' (Griffiths and Gordon, 2003) in vegetative swards of tropical pasture grass species. Hughes et al (1991) and Laca et al (1993) also found that bite area decreased in response to the increase in grazing resistance of the swards but a maximum bite force was not detected.…”
Section: Bite Dimensions and Selectivity Regulationcontrasting
confidence: 90%
“…Previous studies on temperate species did not find evidence to support the 'submit maximum bite force hypothesis' either (Griffiths and Gordon, 2003). Benvenutti et al (2008b) found that bite area and bite force decreased with increasing stem tensile resistance in animals confronted with a horizontal barrier of stems despite the fact that they were able to apply a higher bite force and avoid such a reduction in bite area.…”
Section: Bite Dimensions and Selectivity Regulationmentioning
confidence: 87%
See 1 more Smart Citation
“…, 1995). However, this holistic approach lacks empirical support (Griffiths and Gordon, 2003). A related approach, which has produced clear results, is based on the mechanical properties of the herbage in the vertical and horizontal dimensions (Flores et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that additional factors influence dry matter intake. These include sward height and density (2,7), cell wall or neutral detergent fiber concentration (11), the digestibility of the cell wall (15), and factors related to animal preference for a feed (3). Factors other than the quantity of available pasture may have influenced results in a study by Casler et al (6), who found that apparent intake of orchardgrass and meadow fescue by dairy cows often exceeded that of tall fescue despite having lower available forage.…”
Section: Introductionmentioning
confidence: 99%